Derivation of total ozone amount in the Antarctic atmosphere from TOVS of TIROS-N/NOAA satellites - Takashi Yamanouchi (Antarctic Record, 1984)
A simple regression method is applied to derive the total ozone amount from the TOVS data of TIROS-N/NOAA meteorological satellites received at Syowa Station, Antarctica. Besides channel 9 located in the ozone 9.6μm band, channels 1,2,3 and 8 of HIRS/2 are used. Regression coefficients are determined against Dobson measurements at Syowa Station. Data from 50 orbits of NOAA-6 and -7 are analyzed for 1981-1982. RMS errors of retrieved ozone amounts are 3 to 13 DU ((10)^<-3>・atm・cm) at Syowa Station. Horizontal distributions of the total ozone amount are also given and fairly good agreements are seen at the South Pole between the ozone amounts derived from satellites and ground Dobson measurements.